Nuzhat al-zāhid : Adʿiya-yi maʾthūr az imāmān-i maʿṣūm (ʿalayhim al-salām) bā tawḍīḥāt-i fārsi-yi sada-yi shishum - Jaʿfariyān, Rasūl (Miras Maktoob, ISBN: 9789004365452., 2018)
Together with Shaykh Ṭūsī's (d. 460/1067) Miṣbāḥ al-mutahajjid and ʿAlī al-Tamīmī's (early 6th/12th cent.) Dhakhīrat al-ākhira , the anonymous Nuzhat al-zāhid (ca. 600/1200) is among the oldest surviving testimonies of Duʿāʾ literature among the Shīʿa. As such, it can be regarded as a connecting link between Ṭūsī and the later tradition of Shīʿī Duʿāʾ literature, after Ibn Ṭāwūs (d. 664/1266). The Nuzhat al-zāhid is important because besides Ṭūsī's Miṣbāḥ it also uses other older sources, which often allows the author to provide much more detail than him, adding new material as well. In this sense, the Nuzhat al-zāhid can truly be regarded as a major reference in its field. It is a complete work, covering all the aspects of petitionary prayer in the life of the believer. Written in the sweet kind of language of its times, its explanations constitute a fine example of medieval Persian spiritual prose.